مخدوم محمد ہاشم ٹھٹھویؒ کی بے مثال فقہی تالیف: فاکھة البستان - محمد احمد رضا (FIKR-O NAZAR فکر ونظر, 2014)
The article attempts to introduce an unexplored manuscript of a well known Sindhi hanafi jurist of the medieval age, Makhdum Hashim thathvi. The manuscript that bears the title Fakiha al-Bustan, deals with the legal prescriptions on slaughtering, preying and identification of halal and haram animals. While focusing on the various aspects of its methodology, the article reveals that the work understudy had been produced after consulting a wide range of academic works available at that time, a fact that sheds light on the highly prolific personality of the scholar.